PAUD Teachers Encouragement Strategies in Facing the Dynamics of Online Learning - Safrizal Safrizal; Resti Yulia (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
The pandemic condition has influenced policies in the world of education, especially the problem of changing learning system policies. Starting from full online learning to limited face-to-face learning, even some schools according to regulations have also conducted face-to-face learning. The changing learning conditions have an impact on the psychology of early childhood students. This study aims to describe the teacher's strategy in encouraging to maintain early childhood learning motivation so that the possibility of learning loss can be minimized. This study uses a qualitative descriptive method, with informants selected by purposive sampling, namely 5 teachers who teach in kindergarten, and 1 student's parent. Data collection was carried out by conducting in-depth interviews, documentation studies, and observations made on teacher activities through WhatsApp snaps. The results showed that some of the encouragement strategies carried out by the teacher were carried out through giving appreciation in the form of praise, gifts, publication of the work, and home visits. This is done to encourage children and motivate them to continue learning during the pandemic.